Structural Elucidation of a Glucan from Trichaster palmiferus by Its Degraded Products and Preparation of Its Sulfated Derivative as an Anticoagulant - Haiqiong Ma; Qingxia Yuan; Hao Tang; Hongjie Tan; Tingting Li; Shiying Wei; Jinwen Huang; Yue Yao; Yaping Hu; Shengping Zhong; Yonghong Liu; Chenghai Gao; et al. (Marine Drugs, 2023)
Echinoderms have been attracting increasing attention for their polysaccharides, with unique chemical structure and enormous potential for preparing drugs to treat diseases. In this study, a glucan (TPG) was obtained from the brittle star Trichaster palmiferus. Its structure was elucidated by physicochemical analysis and by analyzing its low-molecular-weight products as degraded by mild acid hydrolysis. The TPG sulfate (TPGS) was prepared, and its anticoagulant activity was investigated for potential development of anticoagulants. Results showed that TPG consisted of a consecutive α1,4–linked D-glucopyranose (D-Glcp) backbone together with a α1,4–linked D-Glcp disaccharide side chain linked through C-1 to C-6 of the main chain. The TPGS was successfully prepared with a degree of sulfation of 1.57. Anticoagulant activity results showed that TPGS significantly prolonged activated partial thromboplastin time, thrombin time, and prothrombin time. Furthermore, TPGS obviously inhibited intrinsic tenase, with an EC50 value of 77.15 ng/mL, which was comparable with that of low-molecular-weight heparin (LMWH) (69.82 ng/mL). TPGS showed no AT-dependent anti-FIIa and anti-FXa activities. These results suggest that the sulfate group and sulfated disaccharide side chains play a crucial role in the anticoagulant activity of TPGS. These findings may provide some information for the development and utilization of brittle star resources.